Novel polymorphisms in PDLIM3 and PDLIM5 gene encoding Z‐line proteins increase risk of idiopathic dilated cardiomyopathy. Issue 10 (19th August 2019) - Wang, Dongfei; Fang, Juan; Lv, Jialan; Pan, Zhicheng; Yin, Xiang; Cheng, Hongqiang; Guo, Xiaogang
Abstract: Idiopathic dilated cardiomyopathy (IDCM), characterized by ventricular dilation and impaired systolic function, is a primary cardiomyopathy resulting in heart failure. During heart contraction, the Z ‐line is responsible for transmitting force between sarcomeres and is also a hot spot for muscle cell signalling. Mutations in Z ‐line proteins have been linked to cardiomyopathies in both humans and mice. Actinin‐associated LIM protein (ALP) and enigma homolog protein (ENH), encoded by PDLIM3 and PDLIM5, are components of the muscle cytoskeleton and localize to the Z ‐line. A PDLIM3 or PDLIM5 deficiency in mice leads to dilated cardiomyopathy. Since PDLIM3 and PDLIM5 are candidate IDCM susceptibility genes, the current study aims to investigate whether polymorphisms within PDLIM3 and PDLIM5 could be correlated with IDCM. We designed a case‐control study, and exons of the PDLIM3 and PDLIM5 were amplified by polymerase chain reactions in 111 IDCM patients and 137 healthy controls. We found that five synonymous polymorphisms had statistical distribution differences between IDCM patients and controls, including rs4861669, rs4862543, c.731 + 131 T > G, c.1789‐3 C > T and rs7690296, according to genotype and allele distribution. Haplotype G‐C‐C‐C and A‐T‐C‐T (rs2306705, rs10866276, rs12644280 and rs4635850 synthesized) were regarded as risk factors for IDCM patients when compared with carriers of other haplotypes (all P < .05). Furthermore, IDCM patients with two novel polymorphisms (c.731 + 131 T > G and c.1789‐3 C > T) had lower systolic blood pressure. In conclusion, these five synonymous polymorphisms might constitute a genetic background that increases the risk of the development of IDCM in the Chinese Han population.